New Insights Into an Overlooked Entity: Long-Term Outcomes of Membranous Lupus Nephritis From a Single Institution Inception Cohort - Kapsia, Eleni; Marinaki, Smaragdi; Michelakis, Ioannis; Liapis, George; Sfikakis, Petros P.; Tektonidou, Maria G.; Boletis, John (Frontiers in Medicine, 2022)
Introduction Pure membranous lupus nephritis (MLN) accounts for 10-20% of total cases of lupus nephritis and is generally associated with a better patient and renal survival compared to proliferative classes. Studies of MLN are limited by small sample size and heterogeneity of included populations since patients with pure MLN and those with mixed classes are usually examined together. Aim of the study To describe clinical and laboratory characteristics of patients with pure MLN, therapeutic regimens, response to treatment, renal relapses and their long-term renal survival and to define prognostic factors of remission and relapse. Methods We retrospectively studied an inception cohort of 27 patients with histologically proven pure MLN. Clinical, laboratory and therapeutical parameters were recorded at diagnosis, at different time points (3-6-9-12-18-24-36-72 months) during the course of the disease, at time of renal flare and at last follow up visit. Results 48.1% (13/27) of patients were treated with mycophenolic acid (MPA), 29.6% (8/27) with cyclophosphamide (CYC) and 3.7% (1/27) with cyclosporine (all in combination with corticosteroids). Five patients (18.5%) did not receive any immunosuppressive treatment. Mean duration of treatment was 4.7 ±2.3 years. Median time to complete remission was 9 months (IQR 7) and median time to partial remission was 4 months (IQR 4). No clinical or laboratory parameter was found to be significantly associated with time to remission. Time to remission was not significantly affected by either of the two treatment regimens (CYC and MPA) (p=0.43). Renal flare was observed in 6 (22%) of the 27 patients in a median time of 51 months (IQR 63). Proteinuria >1g/24h at 1 year significantly correlated with risk of flare (OR 20, p=0.02). After a median follow up period of 77 months, all patients had an eGFR>60ml/min/1.73m2 (mean eGFR 100±32 ml/min/1.73m2). Conclusions In a small cohort of patients with pure MLN, long-term renal survival was very good. With the limitation of the small sample size, we could not find any baseline clinical, biochemical or therapeutic factor that could predict time to remission. Proteinuria >1g/24h at 1 year should be further examined in larger cohorts as a possible predictor of flare.